Mathematical Literacy in Statistics Following Differentiated Learning Using Outdoor Modeling Mathematics - Kaivida Novi Yosita Aritonang; Sofnidar Sofnidar; Dewi Iriani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Indonesia’s students continue to show low literacy and numeracy performance. In PISA, Indonesia ranked 68th out of 81 countries with a mathematics score of 379. This study describes eighth-grade students’ mathematical literacy in statistics after differentiated learning implemented through the Outdoor Modeling Mathematics (OMM) model. The study was conducted at SMPN 5 Pelepat Ilir in May 2025 using a qualitative descriptive design. Six students were selected purposively from a class of 33 based on learning readiness: high (S1KBT, S2KBT), moderate (S1KBS, S2KBS), and low (S1KBR, S2KBR). Data were collected through a mathematical literacy test and semi-structured interviews and were analyzed using three literacy processes: formulating situations mathematically, employing mathematical concepts, facts, procedures, and reasoning, and interpreting and evaluating mathematical results. The findings show that all six students met the three processes, indicating a high level of mathematical literacy after the intervention.